GASIFIKASI ARANG KAYU UNTUK PEMBANGKITAN TENAGA LISTRIK - Hartoyo Hartoyo; Tjutju Nurhayati Syachri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
An experiment on charcoal gasification for power generation was conducted on a pilot scale of 7.5 KVA. This experiment used 50 kg mixed charcoal species having moisture content of 6.9 %, ash content of 2.5 %, volatile matter of 22.4 % and calorific value of 6733 cal/g.The product gas was run through gas purifier, jet condenser, cyclone, gas cooler and filter. The gas was composed of carbon monoxide (26 to 31%), carbon dioxide (3 to 15%), methane (0 to 1%) with calorific values ranging from 2600 to 4100 cal/g.The produce gas which was assumed to have been purified of tar and water vapour was fed into a power generator.The electric power generated ranged from 200 to 234 Volts at around 2.08 A and a revolution of from 1822 to 2110 RPM. It turned out that these gases still contained tar and water vapour which was observed at the engine, an indication that the gas purifier did not function weel. This is evidenced by the fluctuation of the gas flow rate (from 9.8 to 1277 Nm3/hour).The efficiency of charcoal conversion to electric and heat energy was 11. 7% and 60% respectively for a load of 1.8 KW and 7 hours of operation, and 13,9 % and 50.5 % respectively for a load of 2.8 KW and 7 hours of operation.